PERPETUATION OF RADICAL IDEOLOGY: DEPERSONALIZATION AND AGENCY OF WOMEN AFTER THE BANNING OF HIZBUT TAHRIR INDONESIA - Inayah Rohmaniyah (UIN Raden Mas Said Surakarta, 2020)
This study tries to see the existence of women in Hizbut Tahrir Indonesia in Gorontalo after the issuance of Perppu No. 2 of 2017. Based on qualitative research, wherein data is obtained through interviews and focus group discussions, the results of the study found that members of the HTI Muslimah group, as individuals undergo a process of depersonalization. This process gained legitimacy from religious understanding, especially related to belief in the concept of fatalistic destiny, which has contributed to the perpetuation of patriarchal interpretation. Their determination to hold the Taqiyuddin an-Nabhani book as a single source of teachings has contributed effectively in strengthening the process of depersonalization. The banning of HTI did not weaken the group's identity and depersonalize its members. The ban only shifts their da'wah space; from the public to limited space, from large group targets to the individual using a door to door, utilizing networks of friendship and brotherhood, and placing the role of women more significantly. However, there has also been a change in the level of their depersonalization and compliance due to the access to new technologies and knowledge that encouraged them to have critical thinking, modalities, and power to internalize more relevant knowledge and identity.